Decision Support System for Culinary Tourism Recommendations in Batubara Regency Using the Simple Additive Weighting - Elvie Yanti; Risnawati Risnawati; Endra Saputra (SAINTIS Publishing, 2025)
Batu Bara Regency has significant culinary tourism potential, featuring a variety of traditional dishes such as gulai asam ikan and cumi isi pulut. However, culinary data management by the Youth, Sports, Culture, and Tourism Office (DISPORABUDPAR) is still manual and relies solely on visitor numbers. This study develops a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to provide more objective culinary recommendations based on six criteria: food price, facilities, cleanliness, service, menu variety, and location accessibility. Data were collected through observation, interviews, and questionnaires from 47 tourists. The system identified the top three culinary destinations: RM 100 (0.92), Buffet Mangga (0.838), and Kuta Koffee (0.768). Developed using PHP and MySQL, the system has proven to improve the efficiency of culinary data management and assist tourists in making more accurate choices, while also promoting and supporting the equitable development of local culinary tourism.